Chemizm pokopalnianej gleby sulfurozowej w doświadczeniu w warunkach kontrolowanych = Post-mine sulfurous soil chemistry in leaching experiment under controlled conditions at different tree species litter addition - Likus, Justyna; Pietrzykowski, Marcin (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Impact of organic matter on soil chemistry of former Jeziórko sulfur mine was investigated. In research two types of substrate were used: less contaminated (mean 5,090 mg kg-1 S) and high contaminated (42,500 mg kg-1S). Soil substrates were tested with addition of birch or pine litter. The composites (soil substrate + tree litter) were rinsed with water during 12 weeks of experiment. In the obtained leachate pH, EC, DOC (dissolved organic carbon), N, Ca, Mg and S were determined. The results indicate that the rate and amount of leached elements did not depend on litter, but firstly depend on level of sulfur contamination.
Keywords: remediacja; zanieczyszczenie siarką; materia organiczna; ługowanie; remediation; sulfur contamination; organic matter; leaching